Keeping the Beat on the Street : The New Orleans Brass Band Renaissance - Burns, Mick (Book collections on Project MUSE., 2008)
Told in the words of the musicians themselves, Keeping the Beat on the Street celebrates the renewed passion and pageantry among black brass bands in New Orleans. Mick Burns introduces the people who play the music and shares their insights, showing why New Orleans is the place where jazz continues to grow. Brass bands waned during the civil rights era but revived around 1970 and then flourished in the 1980s when the music became cool with the younger generation. In the only book to cover this revival, Burns interviews members from a variety of bands, including the Fairview Baptist Church Brass Band.